Impact of Hepatic Steatosis on the Antiviral Effects of PEG-IFNα-2a in Patients with Chronic Hepatitis B and the Associated Mechanism - Huiqing Liang; Yaoyu Liu; Xiaoqian Jiang; Xiaoting Zheng; Jinmo Tang; Jiaen Yang; Hongli Zhuang; Penghua Lai; Li Peng; Zhenying Guo; Shanshan Cai; Dan Luo; et al. (Gastroenterology Research and Practice)
Objective. To investigate the risk factors for hepatic steatosis in chronic hepatitis B (CHB), to determine its correlation with liver necroinflammation and fibrosis and response to peginterferon alpha-2a (PEG-IFNα-2a) antiviral therapy, and to explore the mechanisms underlying the poor antiviral effect of PEG-IFNα-2a in CHB patients with hepatic steatosis. Methods. We analysed the impact of hepatic steatosis on the antiviral effect of PEG-IFNα-2a on CHB patients in a cohort of 226 patients who underwent pretherapeutic liver biopsy. To assess the complete response (CR), virological response (VR), and biochemical response (BR), the 226 patients were treated with PEG-IFNα-2a for 48 weeks and were followed-up for 24 weeks. The expressions of hepatitis B surface antigen (HBsAg) and hepatitis B core antigen (HBcAg) in the liver tissue were detected in all patients to explore the possible mechanism of hepatic steatosis with regard to antiviral effects. Results. The patients were divided into four groups based on the severity of hepatic steatosis: 119 with no steatosis, 76 with mild steatosis, 22 with moderate steatosis, and 9 with severe steatosis. In the hepatic steatosis groups, the proportions of male patients, patients aged >40 years, patients with hyperuricaemia, patients with a BMI>23 kg/m2, and total cholesterol (TC), triglyceride (TG), glucose (GLU), and uric acid (UA) levels were significantly higher than those in the group without steatosis, whereas the alanine aminotransferase (ALT) and aspartate transaminase (AST) levels were significantly lower than those in the group without steatosis. The multivariate analysis results indicated that a BMI>23 kg/m2 was independently associated with CHB patients with hepatic steatosis; the levels of baseline AST and UA were independently associated with CHB patients with significant hepatic steatosis, and the baseline AST level was independently associated with significant liver fibrosis. After 48 weeks of treatment and 24 weeks of follow-up, the rates of CR, VR, and BR had gradually decreased, whereas the severity of hepatic steatosis had increased. Conclusion. Hepatic steatosis can reduce the efficacy of PEG-IFNα-2a in the treatment of CHB patients, and its mechanism may be related to the different HBcAg expression patterns in liver tissue.